مفهوم الحرية في الإتجاه الليبرالي المساواتي المعاصر (دراسة تحليلية فكرية لمنظور رونالد دوركين) - النائب, أ.د.احسان عبدالهادي; عبدالله, م.م.شهاب أحمد (Sulaimani Journal for Humanities, 2023)
That freedom is not upright on its own - as the theorists of the egalitarian liberal trend argue - but that this value is accompanied by other values, even if they are in different installments, as equality and justice are the other side of the dialectic This study considers that they are moral, political, and legal values that must exist side by side with the value of freedom and accompany it. They are not contradictory values with the value of freedom. This problem has become the focus of the thinkers of the egalitarian liberal trend, especially when (Ronald Dworkin) as one of the most prominent thinkers of this trend and the most profound and influential in contemporary liberal political theories, along with (John Rawls). With the diversifications of contemporary liberal political theory, freedom is one of the core values adopted by liberals, and the most important question posed by egalitarian liberals remains: What about the value of equality? With this question, Ronald Dworkin made equality an important value that corresponds to the value of freedom, and that they are not two independent political and moral ideals that represent the essence of human dignity. In order for political societies to have a legitimate character, these two values must be realized together, by adopting programs and methods that emphasize their complementarity, ensure that they do not conflict, and through which human dignity will be preserved.